Analisis Dampak Pengungkapan Sustainability Report Terhadap Nilai Perusahaan - Shresta Purnamasari; Eny Trimeiningrum (Universitas Katolik Soegijapranata, Semarang, 2022)
To achieve sustainability, a company gets all stakeholders' trust by publishing a Sustainability Report. The report aims to show that their business focuses on and responsible to all stakeholders through economic, environmental, and social dimensions. This study tests the effect of disclosing each dimension on the firm value on 34 listed companies that consistently published Sustainability Reports in 2015-2017. The researchers find that disclosure of economic and social dimensions affects firm value because the company is considered more transparent, has accurate forecasting and analysis, low information asymmetry, gains more trust from investors and debt holders, and meets all stakeholders' expectations. Whereas, disclosure of environmental dimensions does not increase firm value because it is considered prevalent, mandatory, normative, and not attractive to catch the stakeholders' attention. This study complements the diverse findings regarding the benefits of disclosing each activity on firm value in Indonesia. It may occur due to inconsistencies in stakeholders' responses, differences in samples, potential interrelationships between the three dimensions of disclosure endogeneity problems between disclosure with financial performance.